THE CORRELATION BETWEEN KNOWLEDGE AND MENSTRUAL HYGIENE PRACTICES IN CHILDREN WITH EARLY MENARCHE - Permata Lestari, Dewi; Ketut Alit Armini, Ni; Mariyanti, Herdina; Yunitasari, Esti (International Journal of Psychosocial Rehabilitation, 2020)
Background: The average age of menarche gradually experiences a shift. Most children nowadays experience menarche at the age of less than 12 years old. A child experiencing early menarche tends to have no preparation in dealing with menstruation.Purpose: The purpose of this study is to analyze the correlation between knowledge and the practice of menstrual hygiene in children with early menarcheMethod: This study used a cross-sectional approach. The sample population was children with early menarche in elementary school. A total of 49 sample respondents were chosen using the total sampling method. The dependent variable was knowledge of menstruation, and the independent variable was practice of menstrual hygiene. Data were collected using a questionnaire, and a Spearman rank correlation test with a level of significance of α.050.05 was used to analyze the data.Results: The result showed that there is a correlation between knowledge on menstruation and the practice of menstrual hygiene (p = 0.01) with a correlation coefficient (r) = 0.716. There is a strong positive correlation between knowledge of menstruation and practice of menstrual hygiene. The higher the knowledge, the better the menstrual hygiene practice in children with early menarche.Conclusion: It can be concluded that if children with early menarche have high knowledge of menstruation, the practice of menstrual hygiene will likely be good as well.